A systems thinking approach to operating a coal mine: a case study of throughput and value chain integration at Arnot Coal Mine - Mokonyama, Adelaide Ramokone (My University, 2022)
Arnot Coal Mine is a case study for applying systems thinking methodology for managing a complex environment. The Arnot Coal Mine aimed to meet planned production targets at a minimal cost within a specific period. The mine’s production decreased from 2004 until the mine closure. Variable throughput and product qualities led to the mine failing to operate at its potential capacity. This study explored qualitative and quantitative research techniques. The research was based on the systems thinking theory (encompassing the complexity theory) and the Mineral Resource Throughput Management principles. Systems thinking recognises and identifies interconnections, non-linear behaviour, feedback, and dynamic behaviour. Systems thinking is revealed in holism rather than in disintegrated parts. Mineral Resource Throughput Management integrates variability in physical operating conditions, characteristics of the plant process, and the ore’s attributes into the decision-making process and business logic. The study findings confirm that the variability inherent in the geology dictates the throughput and the effectiveness of the processes downstream. The ultimate incomegenerating product is determined by the run of mine quantity and quality as well as interdependent variables and processes. Mining is a non-linear process requiring the recognition of system structure, variables, and the flow (material, information, and synergy) within the entire system. The research aims to understand the operational environment prior to mine closure rather than analysing separate events within individual departments. Therefore, a greater understanding of the value chain allows organisations to understand performance and unlock more potential of the entire system, rather than organisational silos independently. It is, therefore, recommended that feedback loops, emergent properties, system flow, and system behaviour evaluation be significant in continuous improvement and business decision-making. The three dimensions of Mineral Resource Throughput Management should be accounted for by synchronising the physical material flow, logical decision-making, and product payability.
A dissertation submitted in partial fulfilment of the requirements for the degree of Master of Science in Engineering to the Faculty of Engineering and the Built Environment, School of Mining Engineering, University of the Witwatersrand, Johannesburg, 2022